Penerapan Task-Based Language Teaching (TBLT) Dalam Pembelajaran Grammar (Tata Bahasa) Bagi Guru-Guru Di Wilayah Desa Kedung Jeruk - Iwan Ridwan; Sumarta Sumarta; Abdul Kodir Al Baekani; Dani Firmansyah (Pusat Riset dan Inovasi Nasional, 2023)
Grammar is one of components to support the abilities of listening, speaking, reading and even writing. Either learning or teaching the grammar is a rather difficult activity. Some methods were developed by experts, such as Grammar Translation method, students were drilled to comprehend the pattern or formula of a sentence, yet they were stuck when they used it in a verbal communication. Then, coming CLT or Communicative Language Teaching which was said much more better, yet in the reality, the students, of course, much better use their english verbally, nevertheles, they were still confused what pattern they used. Therefore, Task Based Language Teaching or TBLT is one of alternative solutions for both. The students are not merely provided the pattern of sentence but also they can use it verbally in any situational conversation. Besides, in attracting students’ interest in learning grammar, it is integrated to technology called padlet.com as an online application supporting students’ enthuasiasm in learning grammar. After joining this workshop, the teachers can practice the TBLT approach in teaching grammar to their students which is integrated to technology. Thus, it can be concluded that the use of TBLT helps teachers integrate technology, pedagogy, and content knowledge in learning grammar.